First examples of aliphatic zirconium MOFs and the influence of inorganic anions on their crystal structures. Issue 2 (18th September 2014) - Reinsch, Helge; Stassen, Ivo; Bueken, Bart; Lieb, Alexandra; Ameloot, Rob; De Vos, Dirk
Abstract : Three new Zr-MOFs based on aliphatic linker molecules and the role of the anions present during synthesis that affect their framework structures are reported. Abstract : Utilizing the aliphatic linker molecule adipic acid (1, 6-hexanedioic acid, HO2 C–C4 H8 –CO2 H) or 3-methyladipic acid (racemic mixture, HO2 C–C4 H7 CH3 –CO2 H), the first crystalline zirconium adipates were synthesized under aqueous conditions. Their structures were deduced from powder X-ray diffraction data and were confirmed by Rietveld refinements. For all three compounds, the inorganic nodes are related to the well-known Zr6 O4 (OH)4 cluster frequently observed in aromatic zirconium MOFs. Employing ZrOCl2 ·8H2 O and 3-methyladipic acid, a framework withbcu topology was obtained. Starting from adipic acid and Zr(SO4 )2 ·4H2 O, we observed the incorporation of sulfate into the crystal structure. Four sulfate anions are coordinated to each Zr–oxo cluster in a bidentate fashion. In this complex structure, square grids formed by Zr–oxo clusters and adipate anions and furthermore a hydrogen-bonded inorganicdia net can be observed. The third compound presented here is structurally related to the zirconium methyladipate. Using adipic acid and adding CrO4 2− under strongly acidic conditions leads to the incorporation of Cr2 O7 2− into thebcu net. The dichromate anions are coordinated twofold to two different Zr–oxo clusters in a monodentate fashion and thus serve as inorganic connectors between the framework's nodes.